Classical Models for the Bee Simile of Paradise Lost. Issue 1 (2nd January 2019) - Hullinger, David
ABSTRACT: John Milton's famous bee simile in Book One of Paradise Lost is generally known to be modelled on the bee similes of Homer and Virgil, yet the precise nature of this influence is still debated. This article investigates the structural and thematic complexities of Milton's simile and its classical antecedents, particularly examining the relative strength of Homeric and Virgilian influences on Milton. Ultimately, this article argues that Milton's bee simile draws its literary structure and primary function from a passage in Homer's Iliad, but that some of its detail and much of its thematic significance is inspired by the work of Virgil.